Sage 50 accounts for dummies - Kelly, Jane (Chartered management accountant) (--For dummies., 2015)
Recommended by 90% of accountants, Sage 50 Accounts is Europe's best-known small business accounting package. Now completely updated to reflect the latest version of Sage 50 Accounts, this book takes the hassle out of working with the software. In no time, you'll be navigating your way around the new Sage 50 Accounts interface, making sense of the latest changes to backups, and confidently taking control of your business' finances - freeing you up to spend your time managing other areas of your business. It reflects the latest changes in the 2015 edition of Sage 50 Accounts software; shows you how to set up and use Sage 50 Accounts with minimal fuss; provides helpful screenshots to help you every step of the way; offers guidance on going mobile with the Sage 50 app. --